School paper publication in the public elementary schools, Division of City Schools, Manila its status, problems and proposed solutions - Orense, Corazon D. 1923- (s.n.], 1971)
The status of the school paper publication in the public elementary schools of the Division of City Schools in Manila, the problems encountered in the publication of school paper, and the possible solutions to the problems, were determined in this study. The normative-descriptive survey method was used with the questionnaire as the tool in gathering the necessary data. This was supplemented by interviews with some of the respondents involved in the study, and visits to a number of staff rooms in some schools.